2020
DOI: 10.1111/acer.14515
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Analysis of a Randomized Clinical Trial of Naltrexone Among Women Living With HIV: Correlations Between Reductions in Self‐Reported Alcohol Use and Changes in Phosphatidylethanol

Abstract: Background Direct biomarkers such as phosphatidylethanol (PEth) have the capability to detect heavy alcohol use, but it is unclear how strongly self‐reported reduction in alcohol use correlates with reduction in PEth. We sought to explore the strength of correlation between reductions in self‐reported alcohol use and change in PEth among a sample of women living with HIV (WLWH) who participated in a clinical trial to reduce heavy alcohol use. We also sought to determine whether this correlation was stronger in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Our findings are in agreement with the previous literature that showed only weak correlations between change in PEth and change in self-reported number of drinks per day over 7 days (Helander, Hermansson, et al, 2019; McGinnis et al, 2022; Richards, Sajdeya, et al, 2021). It is important to note, that there was a significant correlation between change in PEth and change in drinks per day over 14 days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with the previous literature that showed only weak correlations between change in PEth and change in self-reported number of drinks per day over 7 days (Helander, Hermansson, et al, 2019; McGinnis et al, 2022; Richards, Sajdeya, et al, 2021). It is important to note, that there was a significant correlation between change in PEth and change in drinks per day over 14 days.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported on the relationship between PEth and self-reported alcohol use at one point in time, with most indicating moderate-to-strong correlations from 0.53 to 0.80, although a few studies reviewed in a meta-analysis found weaker correlations from 0.21 to 0.44 (Hahn et al, 2021). A few studies have examined the relationship between change in PEth and change in self-reported alcohol use, with correlations ranging from 0.14 to 0.46 (Helander, Hermansson, et al, 2019; McGinnis et al, 2022; Richards, Sajdeya, et al, 2021).…”
mentioning
confidence: 99%